Actions of Huangqi decoction against rat liver fibrosis: a gene expression profiling analysis. Issue 1 (December 2015) - Zhang, Gui-biao; Song, Ya-nan; Chen, Qi-long; Dong, Shu; Lu, Yi-yu; Su, Ming-yu; Liu, Ping; Su, Shi-bing
Abstract Background Huangqi decoction (HQD) is used for liver fibrosis and cirrhosis treatment in Chinese medicine. This study aims to investigate the pharmacological actions of HQD against liver fibrosis in rats by high-throughput gene expression profiling, network analysis and real-time qRT-PCR. Methods We analyzed the profiles of differentially expressed genes (DEGs) in dimethylnitrosamine (DMN)-induced liver fibrosis in rat. The liver tissue samples of control group (n = 3), model group (n = 3) and HQD group (n = 3) were examined by microarrays. Pathways were analyzed by KEGG. Pathway-gene and protein–protein interaction (PPI) networks were constructed with Cytoscape software. The expression of candidate genes was verified by qRT-PCR.P values less than 0.05 indicated statistical significance. Results Collagen deposition and hydroxyproline (Hyp) content were decreased in the HQD group compared with the model group (P  < 0.001), while that of Hyp in the model group were increased compared with the control group (P  < 0.001). In comparison with the model group, 1085 DEGs (allP  < 0.05, |fold change| >1.5) and 52 pathways in the HQD group were identified. TGF-beta, ECM-receptor interaction, and the cell adhesion molecules pathways were significantly recovered by HQD (P  < 0.001). A pathway-gene network was constructed, including 303 DEGs and 52 pathways, and 514 nodes and 2602 edges, among 142 genes with node degrees greater than 10. The expressions of PDGFra, PDGFrb, PDGFb, PDGFd, COL1A1, COL1A2, COL5A2, and THBS1 were significantly down-regulated by HQD (P  < 0.001). Conclusion HQD down-regulated the expressions of PDGFra, PDGFrb, PDGFb, PDGFd, COL1A1, COL1A2, COL5A2 and THBS1, and TGF-β and PDGF signaling pathways in the DMN-induced liver fibrosis in rats.